PERAN WKSBM DAN PUSKESOS DALAM PENGUATAN PRANATA-PRANATA SOSIAL PERDESAAN - Rusmin Tumanggor (Sosio Informa, 2009)
Institutional spacecraft Community Based Social Welfare (WKSBM) has amounted to eight thousand in Indonesia that spread in various villages and village located in Indonesia. This is the institutions WKSBM Drun rembug centers and efforts for various program activities institu- tions that have found social advance in both the rural social order of the pure form of residents of local villages or village or at the instigation and government facilities. To realize variations larger programs and equitable to the members is required WKSBM the birth of a great arcade form dilakukannnya the WKSBM the various activities of the institutions which became members. Arcade was named the center of social welfare (Puskesos). lf a member is the messenger WKSBM / representatives of all institutions that have existed, while the members consisted of members Puskesos and if necessary WKSBM added from each of the supporting institutions. Thus the social institutions which have rural local wisdom and even the more robust, dynamic, and inte- grated in the activities. On this basis, the village government or urban villages in developing stronger development of its citizens. As propsisi hypothesis "the whole Puskesos in WKSBM and mendistribisikan efforts and programs to its members will be more robust rural social security- related". How the process can be followed in the description of this article.Keyword : center for social walfare, social institution, social capital, social resillience in village.